(untitled) (Journal of Industrial and Mechanical Engineering, 2023)
In Argentina, water level measurement is limited to few water bodies. This situation limits the scope of hydrological and limnological studies. In this framework, the development of low-cost digital limnimeters can be useful, not only for the academic community and decision makers, but also for the development of citizen science initiatives. This work presents the design, construction and pilot test of a low-cost digital limnimeter. The prototype was designed and built with open-source hardware and software and other readily available materials. The equipment operated autonomously for 24 days, recording the water level of the Ing. C. Roggero reservoir (Buenos Aires province, Argentina). The cost of the prototype was lower compared to similar commercial equipment currently available. The experience allowed us to identify opportunities for optimizing the prototype.